2020
DOI: 10.1002/acm2.12978
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of radixact motion synchrony for 3D respiratory motion: Modeling accuracy and dosimetric fidelity

Abstract: The Radixact® linear accelerator contains the motion Synchrony system, which tracks and compensates for intrafraction patient motion. For respiratory motion, the system models the motion of the target and synchronizes the delivery of radiation with this motion using the jaws and multi‐leaf collimators (MLCs). It was the purpose of this work to determine the ability of the Synchrony system to track and compensate for different phantom motions using a delivery quality assurance (DQA) workflow. Thirteen helical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 26 publications
1
70
1
Order By: Relevance
“…Intrafraction motion remains a key challenge in radiation therapy. With a steep learning curve, we have The motion tracking accuracy and dose delivery accuracy were demonstrated adequately, 10,14 ; however, it is still desirable to reconstruct the delivered dose based on actual information (eg, delivered sinogram, real-time motion incorporated images). The current dose reconstruction with PreciseART is based on planned sinogram on pretreatment MVCT, not accounting for actual delivered information such as intrafraction motion, variation in motion tracking, and so forth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrafraction motion remains a key challenge in radiation therapy. With a steep learning curve, we have The motion tracking accuracy and dose delivery accuracy were demonstrated adequately, 10,14 ; however, it is still desirable to reconstruct the delivered dose based on actual information (eg, delivered sinogram, real-time motion incorporated images). The current dose reconstruction with PreciseART is based on planned sinogram on pretreatment MVCT, not accounting for actual delivered information such as intrafraction motion, variation in motion tracking, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Technical details of the Synchrony on Radixact system have been reported elsewhere. 10,13,14 A brief description of the system is provided. The hardware of the system consists of a kV x-ray source and a detector panel mounted with a 90 offset from the MV beam and a camera mounted on the ceiling to capture motion of a set of light-emitting diodes (LEDs) placed on the patient's skin and treatment couch.…”
Section: Technical Description Of the Synchrony Systemmentioning
confidence: 99%
“…Cumulative dose from kV images throughout many Synchrony fractions can be estimated by scaling the per fraction values provided in this work by the total number of images acquired throughout treatment. In an initial study with 13 Synchrony treatment plans with various fractionation schemes, the number of images per fraction ranged from 50 to 206, and the total number of images over all fractions ranged from 310 to 1920, with an average of 810 images 9 . When scaled to 2000 total images, the largest dose to any structure in Table III would be 1.4 Gy (D 1% to the pubic bone for the endothelium patient).…”
Section: Discussionmentioning
confidence: 99%
“…In an initial study with 13 Synchrony treatment plans with various fractionation schemes, the number of images per fraction ranged from 50 to 206, and the total number of images over all fractions ranged from 310 to 1920, with an average of 810 images. 9 When scaled to 2000 total images, the largest dose to any structure in Table III would be 1.4 Gy (D 1% to the pubic bone for the endothelium patient). This value is slightly less than 5% of a typical therapeutic dose of 30, or 1.5 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…However, 4D CT and 4D MRI studies have shown that the amplitude of pancreas movement during breathing is comparable to that of the liver and lungs [ 15 , 16 , 17 ]. For example, Ferris et al demonstrated 5–7-mm root-mean-square displacement of the human pancreas [ 18 ]. To minimize the respiratory motion artifacts, clinical DWI employs rapid acquisition protocols, such as single-shot echo-planar imaging (EPI) following diffusion weighting preparation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%